2006
DOI: 10.1523/jneurosci.4504-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Nogo Receptor Removes Brain Amyloid-β and Improves Spatial Memory in Alzheimer's Transgenic Mice

Abstract: The production and aggregation of cerebral amyloid-␤ (A␤) peptide are thought to play a causal role in Alzheimer's disease (AD). Previously, we found that the Nogo-66 receptor (NgR) interacts physically with both A␤ and the amyloid precursor protein (APP). The inverse correlation of A␤ levels with NgR levels within the brain may reflect regulation of A␤ production and/or A␤ clearance. Here, we assess the potential therapeutic benefit of peripheral NgR-mediated A␤ clearance in APPswe/PSEN-1⌬E9 transgenic mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 45 publications
4
89
0
2
Order By: Relevance
“…Excessive expression of NgR has been shown to prevent α-and β-secretase from cleaving amyloid precursor protein (APP), which reduces the production of Aβ (Park, 2006b). Aβ/APP metabolism is a complex multi-step process involving a variety of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive expression of NgR has been shown to prevent α-and β-secretase from cleaving amyloid precursor protein (APP), which reduces the production of Aβ (Park, 2006b). Aβ/APP metabolism is a complex multi-step process involving a variety of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its suggested role in SCI, NgR1 has been discussed to be involved in neurodegenerative diseases and to possess multiple physiological functions [48][49][50][51][52], for example including regulation of macrophage movement in inflammatory responses [31]. With respect to its involvement in neurodegenerative diseases it was demonstrated that NgR1 directly interacts with Aβ and APP.…”
Section: Relevance Of Ngr1 In Brain Physiology and Further Disease Inmentioning
confidence: 99%
“…With respect to its involvement in neurodegenerative diseases it was demonstrated that NgR1 directly interacts with Aβ and APP. Overexpression of NgR reduces plaque load, and also treatment of APPswe/PSEN-1ΔE9 transgenic mice with the decoy receptor NgR(310)ecto-Fc is able to reduce plaque load and leads to improved spatial memory in these animals [48,49]. In addition, NgR1 may be directly involved in plasticity and synaptic functioning [53,54] and a slower acquisition of a spatial learning and memory task has recently been described for NgR1 (-/-) mice [55].…”
Section: Relevance Of Ngr1 In Brain Physiology and Further Disease Inmentioning
confidence: 99%
“…As Strittmatter outlined in his Keystone presentation, the laboratory had previously shown that the Nogo receptor, known for limiting axon regeneration and repair, binds to the AβPP and to Aβ, but not necessarily oligomers [3,4]. To find proteins that specifically bind to oligomeric species of the peptide, which are now widely believed to be the most toxic Aβ entities, Juha Lauren and colleagues in the laboratory used biotinlabeled oligomers (prepared as per the ADDL method of Bill Klein's group) [5] to screen COS-7 cells expressing a mouse adult brain cDNA library.…”
Section: Partners In Crime -Do Aβ and Prion Protein Pummel Plasticity?mentioning
confidence: 99%